Home automation through voice command and GSM technology - Alam, Sadia Sumaiya; Hossain, Khoteza; Abdullah Al Muntasir (BRAC University, 2015)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2014.